Biomimicry in environmental architecture : Exploring the concept and methods of the bio-inspired environmental architectural design - Ayat Abdulrahim Aljawhary Ahmed Sheta; Ahmed Ahmed Fekry; Baha'a Eldin Hafeth Bakry (Cairo : Ayat Abdulrahim Aljawhary Ahmed Sheta, 2010)
Biomimicry is a new discipline that looks to nature as a model and mentor. One of the most important biomimetic methods of design is the BioTRIZ method, a conflict resolution database that is based on the study of natural ways of unfolding contradictions. This work aims at exploring the concept of Bio-inspired design and its different methodologies
Thesis (M.Sc.) - Cairo University - Faculty of Engineering - Department of Architectural Engineering
Issued also as CD
Keywords: Biomimesis; Biomimicry; Bionics